HUBUNGAN KEPATUHAN PASIEN GAGAL GINJAL KRONIK DENGAN KETERATURAN TINDAKAN HAEMODIALISA DI BLU RSUP PROF Dr. R.D KANDOU MANADO - Yanny Karundeng (Jurnal Ilmiah Perawat Manado (Juiperdo), 2015)
Prevalance of population chronic renal failurein the North Celebes be in the second position of national that is 0,4%. Obedience of the chronic renal failure patient based on the survey on the February 2014 on going haemodialysis treatmen as much as 167 patients, as amount 38,9% don’t followed haemodilysis treatment.Purpose of the research is to knowing relationship between obedience of patient chronic renal failure with haemodialysis treatment as regularly in BLU RSUP Prof. Dr. R.D. Kandou Manado. Type of this research is analytic descriptive with cross sectional approach designs. Population and sample as amount as 64 respondens in Dahlia rooms. Result of the research as following, as much as (98%) respondens obey and regularly, (2%) respondens obey and not regularly, (50%) respondens not obey and obey, and (50%) respondens not obey and not regularly. Result of the Chi Square test showed that there were signidicantly relationship between obedience chronic renal failure patient with haemodialysis treatment as regularly pvalue=0,000<p0,05.Conclusion that obedience chronic renal failure patient significantly relationship with haemodialysis treatment as regularly. Suggestion, hoping to continuously research, so that can be development this research with searching for the other factors had be done, so can met describing as overall about obedience of the ongoing haemodialysis treatment patient